Multiplicity in the experience of voice-hearing: A phenomenological inquiry. (December 2022) - Brewin, Chris R.; Phillips, Kirsty; Morton, John; Mason, Ava J.C.; Saunders, Rob; Longden, Eleanor
Abstract: Although it is recognized that voice-hearers often report a large number and variety of voices there have been few investigations of this multiplicity. Understanding the phenomenology of voice-hearing can provide a firm foundation for theorizing about its causes. In this international online survey of voice-hearers, details were elicited of the content of up to five utterances associated with up to five voices from each respondent. The contents were independently rated and associated with characteristics of each voice such as its perceived age, whether it had changed over time, and whether it was of a familiar person. We investigated predictors (e.g., diagnoses, voice gender, age first heard) of utterance negativity, length, and whether voices referred to themselves. The average number of voices reported was approximately four. The majority were perceived as male and had negative content. Child-aged voices were significantly less negative than all other voices except those perceived as being elderly. Multi-level analyses indicated that there was significant variability at the level of different utterances within voices but variability was more prominent at the level of different voices within an individual. The data were inconsistent with general cognitive models for hearing voices such as the misattribution of inner speech and were more congruent with a dissociation model of voice-hearing. Our findings support approaches based on subtype or dimensional methods of classifying voices, and additionally indicate that research and clinical assessment may benefit from more systematic assessment of multiplicity.